2011
DOI: 10.2174/1874088x01105010170
|View full text |Cite
|
Sign up to set email alerts
|

Study of MG49-PMMA Based Solid Polymer Electrolyte

Abstract: Abstract:The studies of rubber-polymer blends as solid polymer electrolyte for electrochemical devices application have been investigated. The electrolyte films were prepared by solution casting technique. The effect of poly(methyl methacrylate) (PMMA) and lithium tetrafluoroborate (LiBF 4 ), salt concentration on chemical interaction, ionic conductivity, structure and morphology of 49% poly(methyl methacrylate)-grafted natural rubber (MG49) have been analyzed by using fourier transform infrared spectroscopy (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…Reduced XRD intensity is indicative of reduced crystallinity in the samples. Similar observation has also been reported by other authors in other polymer electrolyte systems (Ahmad et al, 2011a;Fonseca et al, 2007). Ahmad et al (2011b) reported that in grafted natural rubber and poly (methyl methacrylate), containing lithium tetrafluoroborate.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Reduced XRD intensity is indicative of reduced crystallinity in the samples. Similar observation has also been reported by other authors in other polymer electrolyte systems (Ahmad et al, 2011a;Fonseca et al, 2007). Ahmad et al (2011b) reported that in grafted natural rubber and poly (methyl methacrylate), containing lithium tetrafluoroborate.…”
Section: Discussionsupporting
confidence: 92%
“…Ahmad et al (2011b) reported that in grafted natural rubber and poly (methyl methacrylate), containing lithium tetrafluoroborate. The degrees of crystallinity in systems of PCLbiodegradable gel polymer electrolyte with LiClO 4 , LiF 3 CSO 3 and LiBF 4 salts decreased nearly linear with increasing the salt concentration (Ahmad et al, 2011a).…”
Section: Discussionmentioning
confidence: 95%
“…MG polymer matrices were simply mixed together with another polymer to produce polymer blend(s) which possess properties that are superior than individual polymers. MG49 has been blended with PMMA [24], PEO [36], PVdF-HFP [37], and PVdF [38]. The chemical structures of PMMA, PEO, PVdF-HFP, and PVdF are shown in Figure 4.…”
Section: Blends Of Pmma-grafted Natural Rubbermentioning
confidence: 99%
“…Ahmad et al [36] found improvement in the conductivity of MG49 with and without LiBF 4 salt upon blending of the polymer with 50 wt.% PMMA. Pure MG49 exhibited ambient conductivity of 1.0 × 10 −12 S cm A polymer blend system that comprised PEO-MG49 with varied wt.% PEO was reported by [39].…”
Section: Blends Of Pmma-grafted Natural Rubbermentioning
confidence: 99%
“…Figure 1 from the MMA and EMA structure in P(MMA-co-EMA). This is because the oxygen atoms from these functional groups can act as electron donor atoms and form a coordinate or dative bond with sodium ions from the doping salts, hence forming a polymer-salt electrolyte [21,22]. Therefore, in these polymer electrolytes systems, the sodium iodide is assumed to be fully dissociated into cations and anions, then coordinated with the polymer host structure.…”
Section: Ftir Analysismentioning
confidence: 99%